Interconnected economies: Assessing the impact of major global stock exchanges and macroeconomic factors on the Indonesian stock market - Abdul Latif; Zulfa Zakiatul Hidayah; Dian Rachmawati Afandi (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The purpose of this study is to examine the influence of global stock exchanges indices—the Dow Jones Industrial Average (DJIA) index, the Shanghai Stock Exchange (SSE) index, and the Nikkei 225 (N225) index—and macroeconomic variables (exchange rate and inflation) on the movement of the Jakarta Composite Index (JCI).Method — The data analysis method used in this study is quantitative causality with the GARCH model technique. The samples include the JCI, global stock exchanges (DJIA, SSE, N225) indices, and macroeconomic variables (exchange rate, inflation) based on monthly secondary data from 2017 to 2022, encompassing 72 months of observation.Result — The results showed that the global stock market variables of the DJIA and the SSE indices had a significant positive effect, while the N225 index had a significant effect on the JCI. Regarding macroeconomic variables, the exchange rate had a significant negative effect, whereas inflation did not affect the JCI.Novelty — The novelty of this research, compared to previous studies, lies in the more recent research period, which spans from 2017 to 2022, and the inclusion of inflation variables, which have not been explored in prior studies.